Cybersecurity operations handbook - Rittinghouse, John W. (Elsevier Digital Press, 2003)
Cybersecurity Operations Handbook is the first book for daily operations teams who install, operate and maintain a range of security technologies to protect corporate infrastructure. Written by experts in security operations, this book provides extensive guidance on almost all aspects of daily operational security, asset protection, integrity management, availability methodology, incident response and other issues that operational teams need to know to properly run security products and services in a live environment. Provides a master document on Mandatory FCC Best Practices and complete coverage of all critical operational procedures for meeting Homeland Security requirements. First book written for daily operations teams Guidance on almost all aspects of daily operational security, asset protection, integrity management Critical information for compliance with Homeland Security.